The effects of real exchange rates and income on international tourism demand for the USA from some European Union countries - Serdar Ongan; Cem Işik; Dilek Özdemir (Economies, 2017)
This paper investigates the effects of real exchange rates and income on inbound tourism demand (tourist arrivals) from Germany, France, the UK, the Netherlands, Italy, Spain, and Sweden to the USA over the period 1996Q3-2015Q1. To achieve this aim, the Harmonized Index of Consumer Prices (HICP) for Restaurants and Hotels was used for the first time-instead of using the general Consumer Price Index (CPI)-to transform the nominal exchange rate into the real exchange rate as an independent variable in tourism demand analysis models. Panel co-integration analysis under the cross-sectional dependence (CD) test and common correlated effects (CCE) approach was applied. Empirical results show that tourists visiting the USA are more sensitive to changes in the real exchange rate than changes in GDP. While French tourists respond highly to the GDP, British tourists respond highly to the real exchange rate. It should also be noted that the UK, having the highest responsiveness to the real exchange rate, is a country outside the Eurozone and also intends to leave the European Union.
Keywords: F00; F24; F14; Z3; 330; real exchange rate; Harmonized Index of Consumer Prices for Restaurants and Hotels (HICP); GDP; tourism demand